8-Hydroxy-2-methylquinolinium tetrachlorido(quinolin-8-olato-kappa N-2,O) stannate(IV) acetonitrile monosolvate - Vafaee, M.; Mohammadnezhad, G.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title solvated salt, (C10H10NO)[SnCl4(C9H6NO)]center dot-CH3CN, the Sn-IV atom is chelated by the N,O-bidentate 8-hydroxyquinolinate ligand and four chloride ions, generating a distorted SnONCl4 octahedral coordination geometry for the metal. In the crystal, the cations are linked to the anions and the solvent molecules by O-H center dot center dot center dot O and N-H center dot center dot center dot N hydrogen bonds, respectively.